Gavi Support for Typhoid Conjugate Vaccines: Moving From Global Investments to Country Introduction. (29th July 2020) - Soble, Adam; Patel, Zeenat; Sosler, Stephen; Hampton, Lee; Johnson, Hope
Abstract: Nine years elapsed between Gavi's investment decision to support typhoid conjugate vaccines (TCVs) in 2008 and Gavi support becoming available for countries to introduce TCV. The protracted path toward Gavi support for TCV highlights the challenges of vaccine development for lower-income countries and the importance of Gavi engagement as early as possible in product development processes to support the alignment of manufacturing, global policy, and program implementation. Early engagement would provide inputs to inform strategic vaccine investment decisions that transition more efficiently toward country implementation. Several countries have been approved for Gavi support to introduce TCV in 2019–2020. The paucity of generalizable typhoid epidemiological data in early introducing countries has reinforced the need for continued evidence generation regarding typhoid epidemiology and TCV impact. This has led to the development of guidance and tools to support country decision making for TCV introduction based on enhanced understanding of local typhoid burden and risk.